“Politics as usual?”-The influence of the internet on political values, attitudes, and behaviour in South Africa : A mixed study approach. - Trossbach, Anne Roswitha (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.